2020
DOI: 10.1098/rsta.2019.0329
|View full text |Cite
|
Sign up to set email alerts
|

On the changes in surface ozone over the twenty-first century: sensitivity to changes in surface temperature and chemical mechanisms

Abstract: In this study, we show using a state-of-the-art Earth system model, UKESM1, that emissions and climate scenario depending, there could be large changes in surface ozone by the end of the twenty-first century, with unprecedentedly large increases over South and East Asia. We also show that statistical modelling of the trends in future ozone works well in reproducing the model output between 1900 and 2050. However, beyond 2050, and especially under large climate change scenarios, the statistical model results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
1
31
0
3
Order By: Relevance
“…According to recent studies, tropospheric O 3 concentration is beginning to stabilize [ 4 , 5 , 6 ]; nevertheless, the current O 3 levels reduce plant photosynthesis and growth rates and decrease potential agricultural productivity in many areas of the world [ 7 , 8 , 9 ]. Average O 3 concentrations vary between 14.5 and 70.1 ppb during the growing season in the forests of Europe [ 10 ], but during heat waves O 3 concentrations can be even higher [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, tropospheric O 3 concentration is beginning to stabilize [ 4 , 5 , 6 ]; nevertheless, the current O 3 levels reduce plant photosynthesis and growth rates and decrease potential agricultural productivity in many areas of the world [ 7 , 8 , 9 ]. Average O 3 concentrations vary between 14.5 and 70.1 ppb during the growing season in the forests of Europe [ 10 ], but during heat waves O 3 concentrations can be even higher [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). In addition to forecasted more frequent and intense heatwaves 13,14 , this lockdown is an observation-based reminder of this potential negative feedback 15 were neither stopped nor restrained. We can therefore reasonably assume business-as-usual ammonia concentrations, and since the formation regime of nitrate in Paris has previously been found to be NO xlimited 17 , a change of regime to NH 3 -limited is highly unlikely.…”
Section: Compare Apples With Applesmentioning
confidence: 94%
“…To assess whether the potential intensification of iodine emissions in the future will have a tangible effect on the ozone layer, we designed a sensitivity experiment (to verify the sensitivity of ozone to iodine) in which all iodine emissions are doubled to present-day emissions (2 × iodine). In essence, it could be considered as a worst-case scenario due to a huge discrepancy between scenarios for the future evolution of iodine precursors like tropospheric ozone (Archibald et al, 2020) and SST (Taylor et al, 2012), despite no dramatic forecast of iodine emission's evolution was made by Iglesias-Suarez et al (2020). The sensitivity of ozone to increase of the iodine emissions we characterized by comparing experiments with 2 × and 1 × loading of iodine.…”
Section: Conducted Experimentsmentioning
confidence: 99%
“…This is in addition to a simultaneous increase in SST due to global warming with correspondingly enhanced metabolic rates of oceanic biota. While the future surface ozone evolution has a large spread in model projections over the 21 st century (Archibald et al, 2020) resulting in a large uncertainty in future iodine emissions, the continuous increase in surface temperatures is predicted to raise tropospheric iodine levels throughout the 21 st century based on Representative Concentration Pathway (RCP) scenarios (Iglesias-Suarez et al, 2020). Klobas et al (2021) showed that in future scenarios the effectiveness of iodine for ozone depletion is poorly sensitive to changes in the state of the stratosphere indicating an increase of relative importance of iodine over other halogens.…”
Section: Introductionmentioning
confidence: 99%